High borosilicate glass and preparation method thereof
By using zinc-modified glass micropowder and clarifier in the preparation process of boron silicate glass, combined with magnetic field and ultrasonic treatment, the problem of uneven composition caused by boron volatility is solved, and the performance and acid and alkali resistance of the glass are significantly improved.
Patent Information
- Application Number
- CN202411272433.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
During the preparation process of borosilicate glass, the boron volatility is high, resulting in uneven composition and uneven structure, which affects the quality and performance of the glass.
Use zinc-modified glass powder and clarifiers with sodium sulfate, cerium oxide, yttrium trioxide, carbon powder, calcium fluoride and other components to be fully mixed at high temperature through magnetic field action, combined with ball milling and ultrasonic treatment to reduce boron volatility. And improve glass performance through specific annealing processes.
It significantly reduces the volatility of boron, improves the uniformity of the composition and performance of the glass, and enhances the resistance to thermal shock and acid and alkali resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass preparation, and in particular relates to high borosilicate glass and a preparation method thereof. Background Art
[0002] Compared with ordinary glass, high borosilicate glass has obvious advantages. High borosilicate glass is a special glass material with low expansion rate, high temperature resistance, corrosion resistance, and good chemical stability. It has excellent performance and is widely used in many fields such as solar energy, chemical industry, pharmaceutical packaging, electric light source, etc., with broad application prospects.
[0003] However, due to the characteristics of boron, during the preparation of high borosilicate glass, boron volatilizes due to heat, resulting in uneven composition, which ultimately leads to structural uneven defects such as phase separation and peeling in the glass, affecting the quality and uniformity of the glass, as well as the overall performance of the glass. Generally speaking, during the heating and melting process, the volatilization of boron is around 10% to 20%. When boron atoms enter the glass network structure and are fixed in the structure, the volatilization will decrease.
[0004] Patent CN110117156B discloses a method for preparing a high borosilicate explosion-proof glass cover, which first uses silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, lithium oxide, potassium oxide, barium oxide, zinc oxide, and ferric oxide as raw materials, and then heats them at high temperatures to form a uniform bubble-free glass liquid. The molten glass liquid is transformed into a solid product with a fixed shape through a mechanical forming method, and then the thermal stress in the glass is eliminated through annealing. The glass is tempered by an air-cooled quenching process. Finally, combined with the surface flatness treatment process, the forming process is improved, and the mold design is subjected to anti-deformation treatment. The forming temperature is strictly controlled to ensure that the deformation is consistent during forming. However, this patented technology still has the problem of high boron volatility, and the performance of the resulting glass product is average. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a high borosilicate glass and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing high borosilicate glass, the specific steps are as follows: (1) In parts by weight, the following components are mixed evenly and heated to melt to obtain glass liquid, which is then cooled and quenched with water to obtain glass particles: 72-75 parts SiO 2 , 8 to 10 parts of Na 2 O, 4 to 5 parts of Al 2 O 3 , 1-2 parts of MgO; (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; (4) In parts by weight, add zinc-modified glass powder, B 2 O 3 Mix all components except the clarifier evenly and heat to melt, apply a magnetic field, add zinc modified glass powder, B 2 O 3 and a clarifier, heat preservation, cooling, forming, and annealing to obtain the high borosilicate glass; the specific formula is: 72-75 parts SiO 2 , 8 to 10 parts Na 2 O, 4 to 5 parts of Al 2 O 3 , 4-5 parts ZnO, 1-2 parts MgO, 1-1.2 parts BaO, 0.8-1 parts ZrO 2 , 0.7~0.9 parts Bi 2 O 3 , 0.5~0.6 parts Ta 2 O 5 , 0.5~0.6 parts Sb 2 O 3 , 0.3~0.4 parts Nb 2 O 5 , 0.3-0.4 parts CeO 2 , 0.3~0.4 parts Y 2 O 3 , 3-4 parts zinc modified glass powder, 12-15 parts B 2 O 3 , 0.5 to 0.7 parts of clarifier.
[0007] Preferably, in step (1), the heating and melting process conditions are: temperature 1600-1700° C., time 5-7 hours.
[0008] Preferably, in step (1), the particle size of the glass particles is 2 to 3 mm.
[0009] Preferably, the specific method of step (2) is: mixing the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.3-0.5, treating with a microwave at 300-500W for 2-3 minutes to obtain a premix, and then mixing the premix with a ball milling medium and ball milling; wherein the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 1-2 parts by weight of sodium silicate and 2-3 parts by weight of polyethylene glycol in 100 parts by weight of water.
[0010] Further preferably, the mass ratio of the premix to the ball milling medium is 1.3-1.5:0.9-1.1; and the ball milling medium is a zirconium bead with a diameter of 0.3-0.5 mm.
[0011] More preferably, the process conditions of ball milling are: 1000-1200 r / min for 10-12 hours.
[0012] Preferably, in step (3), the specific method of pretreatment is: first, add the glass powder to a sodium hydroxide solution with a mass concentration of 8% to 10%, treat it with ultrasonic oscillation at 300 to 500W for 20 to 30 minutes, centrifuge to obtain a precipitate, wash it with water until it is neutral, then add it to an ammonium bifluoride solution, treat it with ultrasonic oscillation at 300 to 500W for 30 to 40 minutes, centrifuge to obtain a precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing hydrofluoric acid with a mass concentration of 48%, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0013] More preferably, the usage ratio of glass powder, sodium hydroxide solution and ammonium bifluoride solution is 20-22 g: 180-200 mL: 190 mL.
[0014] Preferably, in step (3), the ratio of the amount of pretreated glass powder to the reaction solution is 1 g: 15-20 mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.3-0.4 mol / L, 0.3-0.4 mol / L and 0.2-0.3 mol / L, respectively.
[0015] Preferably, in step (3), the specific method of the reaction is: adding the pretreated glass powder to the reaction solution containing zinc salt, treating with 300-500W ultrasonic oscillation for 30-40 minutes, adding 1-1.2 mol / L sodium borohydride aqueous solution dropwise under stirring conditions of 100-200 r / min, and continuing to stir for 10-15 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:8-10mL.
[0016] Preferably, in step (3), after the reaction is completed, the precipitate is centrifuged, washed with water 3 to 4 times, and dried.
[0017] Preferably, in step (4), the heating and melting process conditions are: temperature 1600-1700° C., time 3-4 hours.
[0018] Preferably, in step (4), the magnetic field strength is 10-12T.
[0019] Preferably, in step (4), the clarifier is obtained by uniformly mixing the following components in parts by weight: 1 part of sodium sulfate, 0.3-0.4 parts of cerium oxide, 0.2-0.3 parts of yttrium trioxide, 0.7-0.8 parts of carbon powder, and 0.9-1.1 parts of calcium fluoride; the particle size of the clarifier is 200-300 mesh.
[0020] Preferably, in step (4), the insulation time is 60 to 80 minutes, and the magnetic field strength is kept constant during the insulation.
[0021] Preferably, in step (4), the mixture is naturally cooled to 1200-1250° C. and mechanically formed to obtain a fixed shape.
[0022] Preferably, in step (4), the annealing process conditions are: heating to 800-850°C at 10-15°C / min, annealing for 30-40 minutes; naturally cooling to 600-650°C, annealing for 40-50 minutes, and naturally cooling to room temperature.
[0023] A high borosilicate glass is obtained by the above-mentioned preparation method.
[0024] Compared with the prior art, the present invention has the following beneficial effects: The present invention firstly uses SiO 2 、Na 2 O、Al 2 O 3 , MgO as raw materials to prepare zinc modified glass powder; then the formula amount of SiO 2 、Na 2 O、Al 2 O 3 、ZnO、MgO、BaO、ZrO 2 、Bi 2 O 3 、 2 O 5 , Sb 2 O 3 , Nb 2 O 5 、CeO 2 , Y 2 O 3 Mix well and heat to melt, apply magnetic field, add zinc modified glass powder, B 2 O 3 and clarifier, heat preservation, cooling, forming and annealing to obtain a high borosilicate glass with excellent properties.
[0025] Specifically, the present invention firstly converts SiO 2 、Na 2 O、Al 2 O 3, MgO are uniformly mixed and heated to melt to obtain glass liquid, cooled, quenched with water to obtain glass particles; the glass particles are ball-milled under the dispersion effect of sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; the glass micropowder is pretreated to obtain pretreated glass micropowder, and the pretreated glass micropowder is added to a reaction solution containing zinc salt to react to obtain zinc-modified glass micropowder. The zinc-modified glass micropowder contains the main components of the target glass product, has a micro-nano particle size, has a certain adsorption capacity, reduces the volatilization of boron in a high temperature environment, promotes the full mixing of the components, and is beneficial to improving product performance.
[0026] In the process of glass preparation, a part of the raw materials are first mixed evenly and heated to melt, a magnetic field is applied, and then zinc-modified glass powder, B 2 O 3 and clarifier, combined with the effect of magnetic field, the components can be fully mixed in a relatively short time, boron volatilization can be reduced, the clarification effect is good, and the product performance is further improved.
[0027] The clarifier of the present invention is prepared by mixing sodium sulfate, cerium oxide, yttrium trioxide, carbon powder, calcium fluoride and the like, and has a better clarification effect on the high borosilicate glass liquid of the present invention, thereby ensuring product performance. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Unless otherwise specified, all commodities in this invention are purchased through market channels.
[0030] Example 1 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.72 kg SiO 2 , 0.08kg Na 2 O, 0.04kg Al 2 O 3 , 0.01kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1600°C, time 5 hours.
[0031] The particle size of the glass particles is 2 mm.
[0032] (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; The specific method is: mix the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.3, treat it with a 300W microwave for 2 minutes to obtain a premix, and then mix the premix with a ball milling medium for ball milling; wherein, the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 0.1kg of sodium silicate and 0.2kg of polyethylene glycol 400 (purchased from Guangdong Jihe New Materials Co., Ltd.) in 10kg of water.
[0033] The mass ratio of the premix to the ball milling medium is 1.3:0.9; the ball milling medium is zirconium beads with a diameter of 0.3 mm.
[0034] The process conditions of ball milling are: 1000r / min ball milling for 10 hours.
[0035] (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; The specific method of pretreatment is: first add 2kg of glass powder into 18L of 8% sodium hydroxide solution, treat it with 300W ultrasonic oscillation for 20 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, then add it into 19L of ammonium bifluoride solution, treat it with 300W ultrasonic oscillation for 30 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing 48% hydrofluoric acid, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0036] The dosage ratio of pretreated glass powder to reaction solution is 1g:15mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.3mol / L, 0.3mol / L and 0.2mol / L respectively.
[0037] The specific reaction method is: add the pretreated glass powder to the reaction solution containing zinc salt, treat it with 300W ultrasonic oscillation for 30 minutes, add 1mol / L sodium borohydride aqueous solution drop by drop under the stirring condition of 100r / min, and continue stirring for 10 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:8mL.
[0038] After the reaction was completed, the precipitate was collected by centrifugation, washed 3 times with water and dried.
[0039] (4) 7.2 kg SiO 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3, 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.3kg zinc modified glass powder, 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0040] The magnetic field strength is 10T.
[0041] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0042] The heat preservation time is 60 minutes, and the magnetic field strength is kept constant while heat preservation.
[0043] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0044] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0045] Example 2 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.75 kg SiO 2 , 0.1kg Na 2 O, 0.05kg Al 2 O 3 , 0.02kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1700°C, time 7 hours.
[0046] The particle size of the glass particles is 3 mm.
[0047] (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; The specific method is: evenly mix the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.5, treat with a 500W microwave for 3 minutes to obtain a premix, and then mix the premix with a ball milling medium for ball milling; wherein, the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 0.2kg of sodium silicate and 0.3kg of polyethylene glycol 400 in 10kg of water.
[0048] The mass ratio of the premix to the ball milling medium is 1.5:1.1; the ball milling medium is zirconium beads with a diameter of 0.5 mm.
[0049] The process conditions of ball milling are: 1200r / min ball milling for 12 hours.
[0050] (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; The specific method of pretreatment is: first add 2.2kg of glass powder into 20L of 10% sodium hydroxide solution, treat it with 500W ultrasonic oscillation for 30 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, then add it into 19L of ammonium bifluoride solution, treat it with 500W ultrasonic oscillation for 40 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing 48% hydrofluoric acid, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0051] The dosage ratio of pretreated glass powder to reaction solution is 1g:20mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.4mol / L, 0.4mol / L and 0.3mol / L respectively.
[0052] The specific reaction method is: add the pretreated glass powder to the reaction solution containing zinc salt, treat it with 500W ultrasonic oscillation for 40 minutes, add 1.2mol / L sodium borohydride aqueous solution drop by drop under stirring conditions of 200r / min, and continue stirring for 15 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:10mL.
[0053] After the reaction was completed, the precipitate was collected by centrifugation, washed 4 times with water and dried.
[0054] (4) 7.5 kg SiO 2 , 1kg Na 2 O, 0.5kg Al 2 O3 , 0.5kg ZnO, 0.2kg MgO, 0.12kg BaO, 0.1kg ZrO 2 、0.09kg Bi 2 O 3 、0.06kg Ta 2 O 5 、0.06kg Sb 2 O 3 、0.04kg Nb 2 O 5 , 0.04kg CeO 2 , 0.04kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.4kg zinc modified glass powder, 1.5kg B 2 O 3 , 0.07kg clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1700°C, time 4 hours.
[0055] The magnetic field strength is 12T.
[0056] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.4 kg of cerium oxide, 0.3 kg of yttrium trioxide, 0.8 kg of carbon powder, and 1.1 kg of calcium fluoride; the particle size of the clarifier is 300 meshes.
[0057] The heat preservation time is 80 minutes, and the magnetic field strength is kept constant while heat preservation.
[0058] It is naturally cooled to 1250°C and mechanically formed to obtain a fixed shape.
[0059] The annealing process conditions are: heating to 850° C. at 15° C. / min, annealing for 40 minutes; naturally cooling to 650° C., annealing for 50 minutes, and naturally cooling to room temperature.
[0060] Example 3 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.73 kg SiO 2 , 0.09kg Na 2 O, 0.045kg Al 2 O 3 , 0.015kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1650°C, time 6 hours.
[0061] The particle size of the glass particles is 2 mm.
[0062] (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; The specific method is: mix the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.4, treat with a 450W microwave for 2 minutes to obtain a premix, and then mix the premix with a ball milling medium for ball milling; wherein the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 0.15kg of sodium silicate and 0.25kg of polyethylene glycol 400 in 10kg of water.
[0063] The mass ratio of the premix to the ball milling medium is 1.4:1; the ball milling medium is zirconium beads with a diameter of 0.4 mm.
[0064] The process conditions of ball milling are: 1100r / min ball milling for 11 hours.
[0065] (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; The specific method of pretreatment is: first add 2.1kg of glass powder into 19L of 9% sodium hydroxide solution, treat it with 500W ultrasonic oscillation for 25 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, then add it into 19L of ammonium bifluoride solution, treat it with 400W ultrasonic oscillation for 35 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing 48% hydrofluoric acid, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0066] The dosage ratio of pretreated glass powder to reaction solution is 1g:17mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.35mol / L, 0.35mol / L and 0.25mol / L respectively.
[0067] The specific reaction method is: add the pretreated glass powder to the reaction solution containing zinc salt, treat it with 400W ultrasonic oscillation for 35 minutes, add 1.1mol / L sodium borohydride aqueous solution drop by drop under stirring conditions of 200r / min, and continue stirring for 12 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:9mL.
[0068] After the reaction was completed, the precipitate was collected by centrifugation, washed 3 times with water and dried.
[0069] (4) 7.3 kg SiO 2 , 0.9kg Na 2 O, 0.45kg Al2 O 3 , 0.45kg ZnO, 0.15kg MgO, 0.11kgBaO, 0.09kg ZrO 2 、0.08kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.06kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.04kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.35kg zinc modified glass powder, 1.4kg B 2 O 3 , 0.06kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1650°C, time 3.5 hours.
[0070] The magnetic field strength is 11T.
[0071] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.35 kg of cerium oxide, 0.25 kg of yttrium trioxide, 0.75 kg of carbon powder, and 1 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0072] The heat preservation time is 70 minutes, and the magnetic field strength is kept constant while heat preservation.
[0073] It is naturally cooled to 1220°C and mechanically formed to obtain a fixed shape.
[0074] The annealing process conditions are: heating to 830° C. at 12° C. / min, annealing for 35 minutes; naturally cooling to 620° C., annealing for 45 minutes, and naturally cooling to room temperature.
[0075] Comparative Example 1 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.72 kg SiO 2 , 0.08kg Na 2 O, 0.04kg Al 2 O 3 , 0.01kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1600°C, time 5 hours.
[0076] The particle size of the glass particles is 2 mm.
[0077] (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; The specific method is: evenly mix the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.3, treat with a 300W microwave for 2 minutes to obtain a premix, and then mix the premix with a ball milling medium for ball milling; wherein, the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 0.1kg of sodium silicate and 0.2kg of polyethylene glycol 400 in 10kg of water.
[0078] The mass ratio of the premix to the ball milling medium is 1.3:0.9; the ball milling medium is zirconium beads with a diameter of 0.3 mm.
[0079] The process conditions of ball milling are: 1000r / min ball milling for 10 hours.
[0080] (3) 7.2 kg SiO 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3 , 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.3kg glass powder, 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0081] The magnetic field strength is 10T.
[0082] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0083] The heat preservation time is 60 minutes, and the magnetic field strength is kept constant while heat preservation.
[0084] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0085] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0086] Comparative Example 2 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.72 kg SiO 2 , 0.08kg Na 2 O, 0.04kg Al 2 O 3 , 0.01kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1600°C, time 5 hours.
[0087] The particle size of the glass particles is 2 mm.
[0088] (2) 7.2 kg SiO 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3 , 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.3kg glass particles, 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0089] The magnetic field strength is 10T.
[0090] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0091] The heat preservation time is 4 hours (due to the larger particle size of the added glass particles, the heat preservation time is extended), and the magnetic field strength is kept unchanged while heat preservation.
[0092] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0093] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0094] Comparative Example 3 A method for preparing high borosilicate glass, comprising the following steps: 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3 , 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kgTa 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0095] The magnetic field strength is 10T.
[0096] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0097] The heat preservation time is 60 minutes, and the magnetic field strength is kept constant while heat preservation.
[0098] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0099] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0100] Comparative Example 4 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.72 kg SiO 2 , 0.08kg Na 2 O, 0.04kg Al 2 O 3 , 0.01kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1600°C, time 5 hours.
[0101] The particle size of the glass particles is 2 mm.
[0102] (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; The specific method is: evenly mix the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.3, treat with a 300W microwave for 2 minutes to obtain a premix, and then mix the premix with a ball milling medium for ball milling; wherein, the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 0.1kg of sodium silicate and 0.2kg of polyethylene glycol 400 in 10kg of water.
[0103] The mass ratio of the premix to the ball milling medium is 1.3:0.9; the ball milling medium is zirconium beads with a diameter of 0.3 mm.
[0104] The process conditions of ball milling are: 1000r / min ball milling for 10 hours.
[0105] (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; The specific method of pretreatment is: first add 2kg of glass powder into 18L of 8% sodium hydroxide solution, treat it with 300W ultrasonic oscillation for 20 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, then add it into 19L of ammonium bifluoride solution, treat it with 300W ultrasonic oscillation for 30 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing 48% hydrofluoric acid, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0106] The dosage ratio of pretreated glass powder to reaction solution is 1g:15mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.3mol / L, 0.3mol / L and 0.2mol / L respectively.
[0107] The specific reaction method is: add the pretreated glass powder to the reaction solution containing zinc salt, treat it with 300W ultrasonic oscillation for 30 minutes, add 1mol / L sodium borohydride aqueous solution drop by drop under the stirring condition of 100r / min, and continue stirring for 10 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:8mL.
[0108] After the reaction was completed, the precipitate was collected by centrifugation, washed 3 times with water and dried.
[0109] (4) 7.2 kg SiO 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3 , 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, add 0.3kg zinc modified glass powder, 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0110] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0111] The heat preservation time is 60 minutes.
[0112] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0113] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0114] Comparative Example 5 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.72 kg SiO 2 , 0.08kg Na 2 O, 0.04kg Al 2 O 3 , 0.01kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1600°C, time 5 hours.
[0115] The particle size of the glass particles is 2 mm.
[0116] (2) ball-milling the glass particles under the dispersion effect of polyethylene glycol aqueous solution to obtain glass micropowder; The specific method is: glass particles and polyethylene glycol aqueous solution are evenly mixed in a mass ratio of 1:0.3, microwaved at 300W for 2 minutes to obtain a premix, and then the premix is mixed with a ball milling medium for ball milling; wherein, the polyethylene glycol aqueous solution is obtained by dissolving 0.2kg of polyethylene glycol 400 in 10kg of water.
[0117] The mass ratio of the premix to the ball milling medium is 1.3:0.9; the ball milling medium is zirconium beads with a diameter of 0.3 mm.
[0118] The process conditions of ball milling are: 1000r / min ball milling for 10 hours.
[0119] (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; The specific method of pretreatment is: first add 2kg of glass powder into 18L of 8% sodium hydroxide solution, treat it with 300W ultrasonic oscillation for 20 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, then add it into 19L of ammonium bifluoride solution, treat it with 300W ultrasonic oscillation for 30 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing 48% hydrofluoric acid, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0120] The dosage ratio of pretreated glass powder to reaction solution is 1g:15mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.3mol / L, 0.3mol / L and 0.2mol / L respectively.
[0121] The specific reaction method is: add the pretreated glass powder to the reaction solution containing zinc salt, treat it with 300W ultrasonic oscillation for 30 minutes, add 1mol / L sodium borohydride aqueous solution drop by drop under the stirring condition of 100r / min, and continue stirring for 10 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:8mL.
[0122] After the reaction was completed, the precipitate was collected by centrifugation, washed 3 times with water and dried.
[0123] (4) 7.2 kg SiO 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3 , 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.3kg zinc modified glass powder, 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0124] The magnetic field strength is 10T.
[0125] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0126] The heat preservation time is 60 minutes, and the magnetic field strength is kept constant while heat preservation.
[0127] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0128] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0129] Comparative Example 6 A method for preparing high borosilicate glass, the specific steps are as follows: (1) 0.72 kg SiO 2 , 0.08kg Na 2 O, 0.04kg Al 2 O 3 , 0.01kg MgO are mixed evenly and heated to melt to obtain glass liquid, cooled, and water quenched to obtain glass particles; The heating and melting process conditions are: temperature 1600°C, time 5 hours.
[0130] The particle size of the glass particles is 2 mm.
[0131] (2) ball-milling the glass particles under the dispersion effect of sodium silicate aqueous solution to obtain glass micropowder; The specific method is: mix the glass particles and the sodium silicate aqueous solution in a mass ratio of 1:0.3, treat with a 300W microwave for 2 minutes to obtain a premix, and then mix the premix with a ball milling medium and ball mill; wherein the sodium silicate aqueous solution is obtained by dissolving 0.1kg of sodium silicate in 10kg of water.
[0132] The mass ratio of the premix to the ball milling medium is 1.3:0.9; the ball milling medium is zirconium beads with a diameter of 0.3 mm.
[0133] The process conditions of ball milling are: 1000r / min ball milling for 10 hours.
[0134] (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; The specific method of pretreatment is: first add 2kg of glass powder into 18L of 8% sodium hydroxide solution, treat it with 300W ultrasonic oscillation for 20 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, then add it into 19L of ammonium bifluoride solution, treat it with 300W ultrasonic oscillation for 30 minutes, centrifuge to obtain the precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing 48% hydrofluoric acid, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
[0135] The dosage ratio of pretreated glass powder to reaction solution is 1g:15mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.3mol / L, 0.3mol / L and 0.2mol / L respectively.
[0136] The specific reaction method is: add the pretreated glass powder to the reaction solution containing zinc salt, treat it with 300W ultrasonic oscillation for 30 minutes, add 1mol / L sodium borohydride aqueous solution drop by drop under the stirring condition of 100r / min, and continue stirring for 10 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:8mL.
[0137] After the reaction was completed, the precipitate was collected by centrifugation, washed 3 times with water and dried.
[0138] (4) 7.2 kg SiO 2 , 0.8kg Na 2 O, 0.4 kg Al 2 O 3 , 0.4kg ZnO, 0.1kg MgO, 0.1kg BaO, 0.08kg ZrO 2 、0.07kg Bi 2 O 3 、0.05kg Ta 2 O 5 、0.05kg Sb 2 O 3 、0.03kg Nb 2 O 5 , 0.03kg CeO 2 , 0.03kg Y 2 O 3 Mix well and heat to melt, apply magnetic field, add 0.3kg zinc modified glass powder, 1.2kg B 2 O 3 , 0.05kg of clarifier, heat preservation, cooling, forming, annealing, and obtaining a high borosilicate glass; The heating and melting process conditions are: temperature 1600°C, time 3 hours.
[0139] The magnetic field strength is 10T.
[0140] The clarifier is obtained by uniformly mixing the following components: 1 kg of sodium sulfate, 0.3 kg of cerium oxide, 0.2 kg of yttrium trioxide, 0.7 kg of carbon powder, and 0.9 kg of calcium fluoride; the particle size of the clarifier is 200 meshes.
[0141] The heat preservation time is 60 minutes, and the magnetic field strength is kept constant while heat preservation.
[0142] It is naturally cooled to 1200°C and mechanically formed to obtain a fixed shape.
[0143] The annealing process conditions are: heating to 800° C. at 10° C. / min, annealing for 30 minutes; naturally cooling to 600° C., annealing for 40 minutes, and naturally cooling to room temperature.
[0144] Test example For comparison purposes, flat glass with a thickness of 5 mm was prepared using the methods of Examples 1 to 3 and Comparative Examples 1 to 6, and then performance tests were performed.
[0145] Thermal shock resistance: JC / T2451-2018 "Borosilicate flat glass", 160℃.
[0146] Acid resistance: GB / T 6581-2007 "Determination of resistance of glass to hydrochloric acid at 100°C by flame emission or atomic absorption spectrometry".
[0147] Alkali resistance: GB / T 6580-2021 "Test method and classification for corrosion resistance of glass to boiling mixed alkali aqueous solutions".
[0148] The test results are shown in Table 1.
[0149] Table 1. Glass performance test results
[0150] It can be seen from Table 1 that the glasses obtained in Examples 1 to 3 have very good thermal shock resistance and acid and alkali resistance.
[0151] The glass powder of Comparative Example 1 is not zinc-modified, the glass particles of Comparative Example 2 are not further processed, the zinc-modified glass powder is omitted in Comparative Example 3, no magnetic field is applied in Comparative Example 4, no sodium silicate is added in Comparative Example 5, and no polyethylene glycol 400 is added in Comparative Example 6. The thermal shock resistance and acid and alkali resistance of the glass are significantly deteriorated, indicating that the specially prepared zinc-modified glass powder and other components of the glass work synergistically to improve the glass properties, and applying a magnetic field during the preparation process is also conducive to further improving the glass properties.
[0152] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing high borosilicate glass, characterized in that: The specific steps are as follows: (1) In parts by weight, the following components are mixed uniformly and heated to melt to obtain glass liquid, which is then cooled and quenched with water to obtain glass particles: 72-75 parts of SiO2, 8-10 parts of Na2O, 4-5 parts of Al2O3, and 1-2 parts of MgO; (2) ball-milling the glass particles under the dispersing effect of a sodium silicate polyethylene glycol aqueous solution to obtain glass micropowder; (3) pre-treating the glass powder to obtain pre-treated glass powder, and then adding the pre-treated glass powder to a reaction solution containing zinc salt to react and obtain zinc-modified glass powder; (4) In parts by weight, the components except zinc modified glass powder, B2O3 and clarifier in the following formula are mixed uniformly and heated to melt, a magnetic field is applied, zinc modified glass powder, B2O3 and clarifier are added, the glass is kept warm, cooled, formed and annealed to obtain the high borosilicate glass; the specific formula is: 72-75 parts of SiO2, 8-10 parts of Na2O, 4-5 parts of Al2O3, 4-5 parts of ZnO, 1 1 to 2 parts of MgO, 1 to 1.2 parts of BaO, 0.8 to 1 parts of ZrO2, 0.7 to 0.9 parts of Bi2O3, 0.5 to 0.6 parts of Ta2O5, 0.5 to 0.6 parts of Sb2O3, 0.3 to 0.4 parts of Nb2O5, 0.3 to 0.4 parts of CeO2, 0.3 to 0.4 parts of Y2O3, 3 to 4 parts of zinc modified glass powder, 12 to 15 parts of B2O3, and 0.5 to 0.7 parts of clarifier.
2. The preparation method according to claim 1, characterized in that: In step (1), the heating and melting process conditions are: temperature 1600-1700° C., time 5-7 hours.
3. The preparation method according to claim 1, characterized in that: The specific method of step (2) is: mixing the glass particles and the sodium silicate polyethylene glycol aqueous solution in a mass ratio of 1:0.3-0.5, treating with a microwave at 300-500W for 2-3 minutes to obtain a premix, and then mixing the premix with a ball milling medium and ball milling; wherein the sodium silicate polyethylene glycol aqueous solution is obtained by dissolving 1-2 parts by weight of sodium silicate and 2-3 parts by weight of polyethylene glycol in 100 parts by weight of water.
4. The preparation method according to claim 1, characterized in that: In step (3), the specific method of pretreatment is: first, add the glass powder to a sodium hydroxide solution with a mass concentration of 8% to 10%, treat it with ultrasonic oscillation at 300 to 500W for 20 to 30 minutes, centrifuge to obtain a precipitate, wash it with water until it is neutral, then add it to an ammonium bifluoride solution, treat it with ultrasonic oscillation at 300 to 500W for 30 to 40 minutes, centrifuge to obtain a precipitate, wash it with water until it is neutral, and dry it; the ammonium bifluoride solution is obtained by uniformly mixing hydrofluoric acid with a mass concentration of 48%, ammonium fluoride, and water in a ratio of 30mL:60g:100mL.
5. The preparation method according to claim 1, characterized in that: In step (3), the ratio of the amount of pretreated glass powder to the amount of reaction solution is 1 g: 15-20 mL; the reaction solution is obtained by dissolving zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in water, and the concentrations of zinc chloride pentahydrate, sodium citrate and polyvinyl pyrrolidone in the reaction solution are 0.3-0.4 mol / L, 0.3-0.4 mol / L and 0.2-0.3 mol / L, respectively.
6. The preparation method according to claim 1, characterized in that: In step (3), the specific method of the reaction is: adding the pretreated glass powder to the reaction solution containing zinc salt, treating with 300-500W ultrasonic oscillation for 30-40 minutes, adding 1-1.2 mol / L sodium borohydride aqueous solution dropwise under stirring conditions of 100-200 r / min, and continuing to stir for 10-15 minutes after the addition is completed; the dosage ratio of the pretreated glass powder to the sodium borohydride aqueous solution is 1g:8-10mL.
7. The preparation method according to claim 1, characterized in that: In step (3), after the reaction is completed, the precipitate is collected by centrifugation, washed with water 3 to 4 times, and dried.
8. The preparation method according to claim 1, characterized in that: In step (4), the heating and melting process conditions are: temperature 1600-1700°C, time 3-4 hours; The magnetic field strength is 10~12T.
9. The preparation method according to claim 1, characterized in that: In step (4), the clarifier is obtained by uniformly mixing the following components in parts by weight: 1 part of sodium sulfate, 0.3-0.4 parts of cerium oxide, 0.2-0.3 parts of yttrium trioxide, 0.7-0.8 parts of carbon powder, and 0.9-1.1 parts of calcium fluoride; the particle size of the clarifier is 200-300 meshes; The heat preservation time is 60 to 80 minutes, and the magnetic field strength is kept constant while heat preservation; Cool naturally to 1200-1250℃ and use mechanical forming to obtain a fixed shape; The annealing process conditions are: heating to 800-850° C. at 10-15° C. / min, annealing for 30-40 minutes; naturally cooling to 600-650° C., annealing for 40-50 minutes, and naturally cooling to room temperature.
10. A high borosilicate glass, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
High-strength heat-resistant glass and preparation method thereof
CN120309168A
